The Concept of Diplomatic Immunity under Conventional Law and Islamic Law: A Comparison (International Journal of Scientific Research and Management (IJSRM), 2025)
This paper examines diplomatic immunity under both conventional law and Islamic law and identifies similarities and differences between the two systems. The paper is based on a qualitative methodology in which data is extracted from journals, books, websites, etc. In analyzing the data obtained from the sources, a content analysis was conducted. It is found that the principles of diplomatic immunity such as personal inviolability, immunity from the jurisdiction of domestic courts, freedom of religion, freedom of movement, protection of diplomatic baggage and couriers, freedom of communication, Inviolability of mission archives and inviolability of mission premises and private residence, as contained and codified in the VDR of 1961 and the VCCR of 1963, which today form the basis of international law, are very similar to the Islamic principle of diplomatic immunity, which has been firmly established since the seventh century. However, a key difference between these two systems is that immunity in Islamic law has largely emerged from the constitution of Islamic law and is consequently based on a distinct legal philosophy, whereas in conventional law it has essentially been developed out of political considerations and accepted by states as a binding rule for their international relations. In other words, it can be said that while both conventional and Islamic law recognize diplomatic immunity, there are crucial differences in its theoretical foundations and practical application. Conventional law, which is rooted in secular principles, focuses on international agreements such as the Vienna Conventions, while Islamic law, which is derived from the Qur’an and Sunnah, emphasizes divine revelation and the importance of respecting treaties and ensuring the safety of envoys.